Agricultural yield and conflict - Ang, James (2020)
This research establishes that the emergence and persistence of intrastate conflict incidence since 1960 are influenced by regional agro-ecological factors captured by the extent of variation in potential crop yield. Our results based on cross-country and grid-level analysis indicate that higher potential crop yield variability within a country that is exogenous to both human intervention and regional culture increases the likelihood of intrastate conflict. Our findings are robust to the inclusion of various geographical, institutional, and potentially confounding economic development correlates.